2006
DOI: 10.1073/pnas.0608718103
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytomegalovirus encodes a stable intron that facilitates persistent replication in the mouse

Abstract: The human cytomegalovirus immediate-early 5-kb RNA previously has been shown to be a stable intron that is not required for efficient replication of the virus in cultured fibroblasts. Here we describe a murine cytomegalovirus 7.2-kb ortholog of the human cytomegalovirus 5-kb RNA. The 5 end of the 7.2-kb transcript maps to a consensus splice-donor site that is conserved among all cytomegaloviruses. We constructed mutant viruses lacking the entire 7.2-kb coding domain, the splice-donor site predicted to function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…The cytoplasmic LAT exists in a nonlinear form, presumably a lariat (Wu et al 1996;Rodahl and Haarr 1997). A similar stable intron is derived from the murine cytomegalovirus (Kulesza and Shenk 2006). Finally, in a recent study it was shown that lariat introns accumulate in the cytoplasm of dbr1Δ yeast cells (Armakola et al 2012).…”
Section: Discussion a Population Of Lariat Sisrnas In The Cytoplasmmentioning
confidence: 99%
“…The cytoplasmic LAT exists in a nonlinear form, presumably a lariat (Wu et al 1996;Rodahl and Haarr 1997). A similar stable intron is derived from the murine cytomegalovirus (Kulesza and Shenk 2006). Finally, in a recent study it was shown that lariat introns accumulate in the cytoplasm of dbr1Δ yeast cells (Armakola et al 2012).…”
Section: Discussion a Population Of Lariat Sisrnas In The Cytoplasmmentioning
confidence: 99%
“…gHV68 virus was generated as was previously described (49). MCMV was obtained from Dr. C. Kulesza (Princeton University, Princeton) and was generated as previously described (50). LCMV was obtained from Dr. D. Homann (University of Colorado, Denver) and was generated as previously described (51).…”
Section: Methodsmentioning
confidence: 99%
“…A recent report by Kulesza and Shenk (21) demonstrated that MCMV encodes a 7.2-kb stable intron that occurs in this vicinity; a less abundant 8.0-kb intron was also reported (21), which would encompass the miRNAs in this cluster (Fig. 3A, inset).…”
Section: Fig 2 Northern Blots Of MCMV Mirnas Rna Was Extracted Fromentioning
confidence: 99%